A biblioteca e a iniciação científica no ensino médio: contribuições do letramento informacional na formação de jovens pesquisadores - Siqueira, Maria Silvério da Silva (2023)
This research proposes a study of information literacy for the development of competence in information of high school students, in effective contact with scientific initiation (CI) and search and use of information sources. Thus, this Dissertation was developed during the Professional Master's Degree in Teaching in Basic Education of the Stricto Sensu Graduate Program (PPGEEB) of the Teaching and Research Applied to Education Center (CEPAE) of the Federal University of Goiás (UFG), among the 2020 and 2023. It considers the school library, as a collaborative space for educational practices, essential for the teaching and learning process. In this context, the joint work between the librarian and the teacher is essential for the development of skills and abilities of young researchers. Therefore, the objective of this research is to demonstrate the importance of information literacy for scientific initiation in high school, through the development of activities aimed at training student researchers. And specifically: a) research the academic production that discusses the topic of scientific initiation and the use of information sources in high school; b) understand how the school library, through the librarian, can help in the development of informational competence, in the training process of young researchers; c) develop information literacy activities for the search and use of information for students in the 2nd year of high school at CEPAE, collaborating with the pedagogical process in scientific initiation; d) contribute to the teaching and learning process, through the production of educational media in video format, which guides the search and use of information sources for high school students. The research is characterized as a case study, of the exploratory-descriptive type, with a qualitative approach. Among the technical procedures, a bibliographic review was carried out to base it on the literature and, supported by the works of Campello (2009) and Gasque (2012, 2020) in the aspect of researcher training, and Freire (1996), among other authors in the area of education. In the field research, a short course on online information sources was carried out. For data collection, a questionnaire was applied, with open and closed multiple-choice questions, on the days of interventions in the classroom. The data obtained were submitted to content analysis. The results indicate that it is possible to carry out actions to stimulate teaching and learning through research, in addition to highlighting the needs of high school students with regard to guidance, support for the effective and adequate use of information sources. The educational product resulting from the research is in video format, entitled: “Online information sources for scientific research: where and how to search”, and which aims to contribute to scientific initiation for the development of information literacy of young researchers